Electronics calculations data handbook - McBrearty, Daniel (Newnes, 1998)
This unique handbook consists of tables compiled as a labour-saving aid for electronics engineers, designers and technicians. The layout and content of these is designed to make them easy to use, and to contain the most valuable but tough to calculate information. Daniel McBrearty compiled this book as a result of bitter experience as an analog designer, initially prototyping and testing the ideas of other folk, and seeking to make those little changes that can make the difference between a good and really excellent circuit, and later doing the whole thing himself. If you don't know off the top of your head the best pair of E24 resistors to make an inverting op-amp stage of 18dB gain (and who does?) then this book will save you hours and protect your sanity in a world in which your calculator always goes missing, and you've forgotten the formula. All the key data needed by electronics designers, engineers and technicians Saves on hours of needless number-crunching Must-have information at a glance.